Expression of adipokines and adipocytokines by epidural adipose tissue in cauda equina syndrome in dogs. (15th July 2022) - Leisengang, Stephan; Gluding, Dennis; Hörster, Julia; Peek, Verena; Ott, Daniela; Rummel, Christoph; Schmidt, Martin J.
Abstract: Background: Compression of epidural adipose tissue (EAT) within the scope of cauda equina syndrome (CES) could lead to an enhanced expression of inflammatory mediators, possibly contributing to pain amplification in dogs. Objectives: To analyze expression of inflammatory adipo(‐cyto)kines within the EAT of dogs with CES. Animals: Client‐owned dogs: 15 dogs with CES and 9 dogs euthanized for unrelated medical reasons (controls). Methods: Prospective, experimental study. Epidural adipose tissue and subcutaneous adipose tissue were collected during dorsal laminectomy and used for real‐time quantitative polymerase chain reaction. Tissue explants were cultured for measurements of inflammation‐induced release of cytokines. Results: Results show a CES‐associated upregulation of the cytokines tumor necrosis factor alpha (TNFα: mean ± SD: 18.88 ± 11.87, 95% CI: 10.90‐26.86 vs 9.66 ± 5.22, 95% CI: 5.29‐14.02, *: P  = .04) and interleukin‐ (IL‐) 10 (20.1 ± 9.15, 95% CI: 14.82‐25.39 vs 11.52 ± 6.82, 95% CI: 5.82‐17.22, *: P  = .03), whereas the expression of the adipokine leptin was attenuated in EAT of dogs with CES (3.07 ± 2.29, 95% CI: 1.80‐3.34 vs 9.83 ± 8.42, 95% CI: 3.36‐16.30, **: P  = .007). Inflammatory stimulation of EAT explant cultures resulted in an enhanced release of IL‐6 (LPS: 5491.55 ± 4438, 95% CI: 833.7‐10 149; HMGB1: 1001.78 ± 522.2, 95% CI: 518.8‐1485; PBS: 310.9 ± 98.57, 95% CI: 228.5‐393.3, ***: P  < .001). Conclusion and Clinical Importance: Expression profile of inflammatory adipo(‐cyto)kines by EAT is influenced from compressive forces acting in dogs with CES and might contribute to amplification of pain.